2017
DOI: 10.1039/c6mh00586a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle/MOF composites: preparations and applications

Abstract: Nanoparticle/MOF materials usually have new or enhanced applications compared with bare MOF or NPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
132
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 302 publications
(135 citation statements)
references
References 131 publications
1
132
0
2
Order By: Relevance
“…[42,43] ZIF-67 has a tunable pore aperture, highly stable structure, and catalytic activity. [14,23,31] For example, Xu and co-workers [47] obtained 1D carbon nanorods via the pyrolysis The applications of carbon and carbon-based materials with high porosity, high surface area, and functionalities based on metal-organic framework precursors and/or templates have attracted significant research interest in recent years, particularly in the field of batteries. [13,14,33] Moreover, carbon hybrids containing nanostructured metal species (e.g., metal oxides (MOs)) are likely to form under in situ carbonization conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[42,43] ZIF-67 has a tunable pore aperture, highly stable structure, and catalytic activity. [14,23,31] For example, Xu and co-workers [47] obtained 1D carbon nanorods via the pyrolysis The applications of carbon and carbon-based materials with high porosity, high surface area, and functionalities based on metal-organic framework precursors and/or templates have attracted significant research interest in recent years, particularly in the field of batteries. [13,14,33] Moreover, carbon hybrids containing nanostructured metal species (e.g., metal oxides (MOs)) are likely to form under in situ carbonization conditions.…”
mentioning
confidence: 99%
“…Traditionally, PC can be obtained via various methods, such as the direct heat treatment of organic precursors, hard template or nanocast methods, and soft template methods. [4,21,[27][28][29][30][31] Since the report on the MOF-templated synthesis of PC in 2008, [32] a large number of studies have been reported on the use of MOFs as suitable precursors/templates for carbon synthesis. [23,25,26] Metal-organic frameworks (MOFs) have drawn wide research interest as a novel class of porous materials that are crystalline materials consisting of metal ions and organic ligands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive analysis of the development of MOF materials. [59] Zhao et al introduced a new MXene-MOF composite Ti 3 C 2 T x -CoBDC (M represents an early transition metal, X stands for carbon and/or nitrogen and T represents the surface groups such as -OH, -O or -F, Figure 3b). [42] MAF-X27-OH 1.0 M KOH 1.47 292 88 [29] USTA-16 1.0 M KOH 1.60 408 77 [33] Co 2 (ptbc) 4 0.05 M phosphate buffer 1.69 671 (2 mA cm À 2 ) - [43] ZIF-67/NPC-2(2 : 1) 0.1 M KOH 1.55 b 410 117 [44] Co(L) 0.5 (adip) 0.…”
Section: Co Mofs and Their Composites For The Oermentioning
confidence: 99%
“…[5][6][7] In addition, electric power, on the basis of a variety of technologies such as electrocatalysis, [8] fuel cells, [9] batteries, [10] or supercapacitors (SCs), [11] is widely considered as another promising energy carrier. [35,36,[43][44][45][46][47][48] This MOF composite strategy could not only expand their applications toward a broad scope which were not achieved by individual components, but also improve their final catalytic performances, originating from the nanoconfinement effect and the synergetic effect between MOFs and the guest species. The energy technologies mentioned above strongly rely on the reasonable design of materials with optimal structures and appropriate functionalities to facilitate the reactions and/or www.advancedsciencenews.com studied.…”
Section: Introductionmentioning
confidence: 99%